Treatment method and application of hard carbon precursor rich in micro-nano aperture structure

Through a hard carbon precursor treatment method rich in micro-nano pore size structure, the problem of closed pores and shrink pores in the high-temperature sintering of biomass materials is solved, the high specific capacity and Coulomb efficiency of hard carbon materials are achieved, and the cycle stability and rate performance of sodium ion batteries are improved.

CN119706785APending Publication Date: 2025-03-28DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775841.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, due to cellulose volatilization during high-temperature sintering of biomass materials, the pore size of the hard carbon material is closed and shrinked, thereby making the material low specific capacity, low Coulomb efficiency and unstable circulation.

Method used

A hard carbon precursor treatment method is adopted that includes crushing the biomass raw material into a dust material, performing oxygen-free precalcination to discharge tar, adding soluble salt solution to fully infiltrate, freezing crystallization, and sublimating water vapor under vacuum environment, followed by high-temperature calcination and cooling, and finally obtaining a hard carbon material rich in micro-nano pore structure by washing and airflow.

Benefits of technology

Through this method, the specific surface area and specific capacity of the hard carbon material are significantly increased, collapse and shrinkage during sintering are reduced, the Coulomb efficiency and cyclic stability of the material are improved, and the storage and rate performance of sodium ions are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706785A_ABST
    Figure CN119706785A_ABST
Patent Text Reader

Abstract

The invention discloses a treatment method and application of a hard carbon precursor rich in a micro-nano aperture structure, and relates to the technical field of sodium ion battery negative electrode materials. According to the preparation method, a soluble salt saturated solution is creatively permeated into a hard carbon precursor material in advance, salt is adopted for occupying the pore diameter forming position in advance, so that the pore diameter structure is protected in the sintering process of the material, collapse and obvious shrinkage are avoided, and then the precursor material is converted into the hard carbon material through high-temperature sintering; and washing and dissolving the crystal particles occupied in advance through an aqueous solution, and removing the crystal particles in the aqueous solution to obtain the porous anhydrous porous hard carbon material. Besides, the porous hard carbon material can promote ion diffusion, improve the interface affinity of the electrode and electrolyte and improve the storage performance of sodium through pore structure regulation and control, and the porous hard carbon material also shows excellent rate capability, namely, the porous hard carbon material can still keep relatively high discharge capacity under high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a method for processing a hard carbon precursor rich in micro-nano pore structures and applications thereof. Background Art

[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, both of which store and release energy through the movement of ions between the positive and negative electrodes. In sodium-ion batteries, sodium ions are released from the positive electrode during charging, move to the negative electrode through the electrolyte and embed, and move in the opposite direction during discharge. For sodium-ion batteries, the negative electrode material is crucial to battery performance. It needs to have good conductivity, chemical stability and high specific capacity to ensure the rapid embedding and de-embedding of sodium ions, thereby improving the battery's charge and discharge efficiency and cycle life.

[0003] Compared with graphite, hard carbon has a larger interlayer spacing, which can adapt to the larger radius of sodium ions (0.102nm), while the interlayer spacing of graphite (0.335nm) limits the intercalation reaction of sodium ions. In addition, hard carbon has the advantages of high sodium storage capacity, good conductivity, low platform potential, small volume change during charge and discharge, and is not easy to pulverize, as well as environmental friendliness and low cost. These characteristics make hard carbon an ideal choice for negative electrode materials of sodium ion batteries.

[0004] During the high-temperature sintering process of biomass materials in the prior art, the cellulose-rich materials volatilize in large quantities, and the pores on the surface and inside of the hard carbon materials are prone to closed pores and shrinkage during the forming process, resulting in fewer and uneven pores in the sintered materials, which in turn makes the material have a lower specific capacity, low coulombic efficiency and unstable cycle.

[0005] Based on the above reasons, this application is hereby filed. Summary of the invention

[0006] In view of the problems or defects in the above-mentioned prior art, the object of the present invention is to provide a hard carbon precursor processing method rich in micro-nano pore structure and application.

[0007] In order to achieve the above-mentioned purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0008] A method for processing a hard carbon precursor rich in micro-nano pore structure, the method specifically comprising the following steps:

[0009] (1) crushing the biomass raw material to a size not exceeding 100 microns to obtain a dust-like material;

[0010] (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized primary carbon material;

[0011] (3) adding the pre-carbonized primary carbon material described in step (2) into a soluble salt solution according to the proportion, and stirring thoroughly until it is completely soaked; freezing the resulting mixed solution to crystallize, and then heating it under a vacuum environment to allow the ice crystals to directly sublimate into water vapor; and then calcining at high temperature, cooling to room temperature, washing with water to remove impurities, and air flow pulverizing in sequence to obtain a hard carbon material rich in micro-nano pore structure.

[0012] Furthermore, in some embodiments, the biomass raw material in step (1) can be one or more of coconut shells, bamboo, hard fruit shells, straw, grass leaves, etc.

[0013] Specifically, in the above technical solution, the purpose of the oxygen-free pre-calcination in step (2) is to discharge the tar in the hard carbon raw material to obtain a pre-carbonized material.

[0014] Furthermore, in the above technical solution, the time for the oxygen-free pre-calcination treatment in step (2) is 3-5 hours, preferably 4 hours.

[0015] Furthermore, in the above technical solution, during the anaerobic pre-calcination treatment in step (2), a protective gas may be introduced into the reaction system to accelerate the discharge of tar by purging with the protective gas.

[0016] Furthermore, in the above technical solution, the flow rate of the protective gas is 1-5 ml / s.

[0017] Furthermore, in the above technical solution, the protective gas is argon.

[0018] Furthermore, in the above technical solution, the soluble salt in step (3) has high stability, for example, sodium chloride (NaCl), potassium chloride (KCl), sodium sulfate (Na 2 SO 4 ) or potassium sulfate (K 2 SO 4 ) any one or more of ).

[0019] Furthermore, in the above technical solution, the volume ratio of the pre-carbonized primary carbon material to the soluble salt solution in step (3) is 1:5-10.

[0020] Furthermore, in the above technical solution, the freezing temperature used for the freeze crystallization in step (3) is -50°C to -30°C.

[0021] Specifically, in the above technical solution, the vacuum degree of the vacuum environment in step (3) is 1 to 10 mbar.

[0022] Furthermore, in the above technical solution, the temperature of the high temperature calcination in step (3) is 1000-1200° C., and the time of the high temperature calcination is 3-4 hours.

[0023] Furthermore, in the above technical solution, the heating rate in step (3) during heating to the high temperature calcination temperature is 1-5°C / min. In some embodiments of the present invention, the heating rate is 2°C / min.

[0024] Furthermore, in the above technical solution, the cooling rate during the cooling to room temperature in step (3) is 1-5°C / min. In some embodiments of the present invention, the cooling rate is 2°C / min.

[0025] Furthermore, in some embodiments of the present invention, in the above technical solution, during the airflow crushing process in step (3), the airflow pressure is controlled to be 0.7 MPa, the feed rate is 2 kg / h, and the gas flow rate is 6 square meters / minute.

[0026] The second object of the present invention is to provide a hard carbon material rich in micro-nano pore structure prepared by the method described above.

[0027] The third object of the present invention is to provide the application of the hard carbon material rich in micro-nano pore structure prepared by the above method in sodium ion batteries.

[0028] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the negative electrode is a hard carbon material rich in micro-nano pore structure prepared by the above-mentioned method.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention adds a large amount of soluble salt solution to fully infiltrate, so that the water in the resulting mixed solution fully occupies the pore size after crystallization, reduces the collapse and obvious shrinkage during the sintering process, and increases the specific surface area of ​​the hard carbon material.

[0031] (2) In the present invention, after ice crystals directly sublimate from solid to gaseous water vapor, the salt solvent crystallizes in the hard carbon gaps and occupies the gaps in advance, thereby reducing the closed pores and shrinkage pores in the gaps during the sintering process and increasing the specific surface area of ​​the hard carbon.

[0032] (3) The present invention innovatively infiltrates a soluble salt solution into the hard carbon precursor material in advance, and uses salts to occupy the pore formation position in advance, so that during the sintering process, the pore structure of the material is protected and does not collapse or shrink significantly. The precursor material is then converted into a hard carbon material through high-temperature sintering. The crystal particles that occupy the position in advance are washed and dissolved by an aqueous solution, and then removed by entering an aqueous solution to obtain a multi-void anhydrous porous hard carbon material.

[0033] (4) The present invention can ensure that the morphology and structure of the material are stably maintained during the freeze-drying process. While vacuum sublimation drying removes the presence of macromolecular water, porous surface characteristics can also be obtained. The porous hard carbon material can promote ion diffusion, improve the interface affinity between the electrode and the electrolyte, and enhance the storage performance of sodium through pore structure regulation. The porous hard carbon material also exhibits excellent rate performance, that is, it can still maintain a high discharge capacity at high current density. At the same time, during the preparation process, the freeze-drying machine is simple and convenient to use and easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The charge and discharge cycle diagram of a half-cell assembled with the hard carbon material rich in micro-nano pore structure prepared in Example 1;

[0035] Figure 2 This is the XRD pattern of the hard carbon material rich in micro-nano pore structure prepared in Example 2. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0037] Based on the information contained in this application, it is easy for those skilled in the art to make various changes to the precise description of the present invention without departing from the spirit and scope of the appended claims. It should be understood that the scope of the present invention is not limited to the defined process, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention. In fact, various changes that the technicians in this field or related fields can obviously make to the embodiments of the present invention are all covered within the scope of the appended claims.

[0038] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0039] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0040] Example 1

[0041] A method for processing a hard carbon precursor rich in micro-nano pore structure in this embodiment specifically comprises the following steps:

[0042] 1. Crushing: Crushing the coconut shell to reduce its particle size to no more than 50 microns to obtain dust-like material.

[0043] 2. Anaerobic pre-calcination: The crushed dust material is sent into a box furnace in an argon atmosphere for pre-carbonization. The material is heated from room temperature, and the temperature is increased by 0.5 degrees Celsius per minute to 550 degrees Celsius for 3 hours. Then the temperature is lowered by 0.5 degrees Celsius per hour to 25 degrees Celsius to obtain a pre-carbonized primary carbon material, and tar is discharged;

[0044] 3. Mixed pre-freezing: first weigh 180g of sodium chloride crystals, add 500mL of distilled water, and fully dissolve to obtain a sodium chloride solution; add the sodium chloride solution to 100g of the pre-carbonized primary carbon material obtained after cooling in step 2, stir well for 5h, and completely infiltrate; place the obtained infiltrated material in a freezer, lower the temperature to -40°C for freeze-drying treatment to freeze and crystallize the water in the material.

[0045] 4. Vacuum sublimation: After ensuring that the water in the frozen crystallized material in step 3 is completely frozen into solid ice crystals, transfer it to the freeze dryer, start the heating system under a vacuum environment, heat the frozen crystallized material to -5°C to 0°C, and allow the ice crystals to sublime directly from the solid state to gaseous water vapor.

[0046] 5. Desorption and drying: The sublimated water vapor is then pumped out with a vacuum pump, and the water vapor pressure in the system is reduced to promote the sublimation of more ice crystals.

[0047] 6. High-temperature calcination: Place the pre-calcined carbonized material into an orbital furnace and heat it up in a step-by-step manner at a rate of 2 degrees Celsius per minute until it reaches 1200 degrees Celsius. Keep it warm for three hours and then cool it down to room temperature at a rate of 2 degrees Celsius per minute.

[0048] 7. Washing and removing impurities: Transfer the material after cooling in step 6 to a reaction container, wash the above-mentioned anhydrous material with deionized water, wash it with water for 10 times to fully wash out the salt solution molecules inserted in the gaps, place it in an oven at 400°C to dry out excess water, and then dry it to obtain anhydrous porous hard carbon.

[0049] 8. Airflow milling: After drying, the material is put into airflow milling for crushing and screening. During the airflow milling process, the airflow pressure is controlled to be 0.7 MPa, the feed rate is 2 kg / h, and the gas flow rate is 6 square meters / minute to obtain a hard carbon material rich in micro-nano pore structure, which can be used directly.

[0050] Example 2

[0051] The present embodiment provides a method for treating a hard carbon precursor rich in micro-nano pore structure, which is basically the same as that of the first embodiment, with the only difference being that the number of water washings in step 7 of the present embodiment is 5 times, and the rest remain unchanged.

[0052] Example 3

[0053] The present embodiment provides a method for processing a hard carbon precursor rich in micro-nano pore structure, which is basically the same as that of the first embodiment, with the only difference being that in step 3 of the present embodiment, 180 g of sodium chloride crystals are replaced with 200 g of potassium chloride and 100 g of sodium sulfate when preparing the solution, and the rest remain unchanged.

[0054] Example 4

[0055] The present embodiment provides a method for processing a hard carbon precursor rich in micro-nano pore structure, which is basically the same as that of Example 1, with the only difference being that in step 3 of the present embodiment, 180 g of sodium chloride crystals are replaced with 200 g of potassium chloride, 100 g of sodium sulfate and 60 g of sodium chloride when preparing the solution, while the rest remain unchanged.

[0056] Example 5

[0057] The present embodiment provides a method for processing a hard carbon precursor rich in micro-nano pore structure, which is basically the same as that of the first embodiment, with the only difference being that the temperature of high-temperature calcination in step 6 of the present embodiment is 1400°C.

[0058] Structural testing:

[0059] Figure 2 This is the XRD pattern of the hard carbon material rich in micro-nano pore structure prepared in Example 2. It can be seen that the prepared material is hard carbon and the added salt does not remain in the subsequent hard carbon material, indicating that 5 water washes are sufficient to remove the salt inserted in the gaps of the hard carbon.

[0060] In addition, the hard carbon prepared by the present invention is rich in micro-nano pore structure, which increases the specific surface area of ​​the hard carbon and further increases the specific capacity of the hard carbon material.

[0061] Electrochemical performance test:

[0062] The hard carbon materials rich in micro-nano pore structures prepared in the above Examples 1-5 are respectively used as negative electrode active materials to assemble into half-cells, and the specific method is as follows:

[0063] The negative electrode plate is composed of a hard carbon material rich in micro-nano pore structure, Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, wherein the mass ratio of the hard carbon material rich in micro-nano pore structure, Super P, SBR and CMC is 90:2:4:4. The composite hard carbon material powder and Super P conductive carbon are ground and mixed evenly for 20 minutes in proportion, and the evenly mixed hard carbon material rich in micro-nano pore structure and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), placed on a micro ball mill and stirred for 15 minutes to obtain a uniform slurry, and the slurry is evenly coated on aluminum foil (the coating amount is 110.23g / cm 2 ), vacuum dried in an oven at 120°C for 5 hours, and punched out negative electrode sheets with a diameter of 12 mm using a gun press, which were weighed and set aside for use.

[0064] A sodium ion battery half-cell is formed by using a sodium sheet as the positive electrode, the negative electrode is the negative electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 180 mA / g, the test voltage range is 0.05 V-2 V, and the half-cell is subjected to a charge and discharge cycle test.

[0065] Table 1 Electrochemical performance test results of button cells assembled with hard carbon materials rich in micro-nano pore structure prepared in Examples 1-5

[0066]

[0067] It can be seen from Table 1 that the amount of overall salt used in Example 4 is larger, and the higher the concentration, the better the first effect of the hard carbon obtained. It can be concluded that the amount of overall salt used is linked to the first cycle charge and discharge performance.

Claims

1. A method for processing a hard carbon precursor rich in micro-nano pore structure, characterized in that: The method specifically comprises the following steps: (1) crushing the biomass raw material to a size not exceeding 100 μm to obtain a dust-like material; (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized primary carbon material; (3) adding the pre-carbonized primary carbon material described in step (2) into a saturated solution of a soluble salt according to a ratio, and stirring thoroughly until it is completely soaked; freezing and crystallizing the resulting mixed solution, and then heating it under a vacuum environment to allow the ice crystals to directly sublimate into water vapor; and then calcining at high temperature, cooling to room temperature, washing with water to remove impurities, and air flow pulverizing in sequence to obtain a hard carbon material rich in micro-nano pore structure.

2. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: The biomass raw material in step (1) can be one or more of coconut shells, bamboo, hard fruit shells, straw, and grass leaves.

3. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: The time of the oxygen-free pre-calcination treatment in step (2) is 3-5 hours.

4. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: The soluble salt in step (3) has high stability, and may be, for example, any one or more of sodium chloride (NaCl), potassium chloride (KCl), sodium sulfate (Na2SO4) or potassium sulfate (K2SO4).

5. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: In step (3), the volume ratio of the pre-carbonized carbon material to the saturated solution of the soluble salt is 1:5-10.

6. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: The freezing temperature used for the freeze crystallization in step (3) is -50°C to -30°C.

7. The method for processing a hard carbon precursor rich in micro-nano pore structure according to claim 1, characterized in that: During the air flow pulverization process in step (3), the air flow pressure was controlled to be 0.7 MPa, the feed rate was 2 kg / h, and the gas flow rate was 6 m2 / min.

8. A hard carbon material rich in micro-nano pore structure prepared by the method according to any one of claims 1 to 7.

9. Application of the hard carbon material rich in micro-nano pore structure prepared by the method according to any one of claims 1 to 7 in sodium ion batteries.

10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a hard carbon material rich in micro-nano pore structure prepared by the method according to any one of claims 1 to 7.